Application of quality function deployment on shelf-life analysis of Agaricus bisporus Portobello. (May 2017) - Djekic, Ilija; Vunduk, Jovana; Tomašević, Igor; Kozarski, Maja; Petrovic, Predrag; Niksic, Miomir; Pudja, Predrag; Klaus, Anita
Abstract: The aim of this study was to analyze application of quality function deployment on examining the shelf-life of Agaricus bisporus Portobello packed in modified atmosphere packaging stored for 22 d at 4 °C. Mushrooms were packaged under three modified atmosphere packaging conditions: high nitrogen packaging (HNP); low carbon dioxide packaging (LCP); low oxygen packaging (LOP). Packaging with air inside initially was used as the atmosphere treatment (AIR). In respect to color changes, total color difference and browning index showed the greatest range for HNP and the smallest range for LOP. Regarding sensory analysis, LOP and AIR had the best results for overall quality compared to LCP and HNP. Odor characteristics were best scored for LOP while AIR had the worst impact on this feature. The highest level of quality deterioration was observed for LCP and HNP mushrooms while AIR mushrooms had the lowest level of deterioration. Quality function deployment showed that the best 'Quality Score' was for LOP, followed by AIR. LCP and HNP had the worst 'Quality Score' during the entire shelf-life. Highlights: Quality deterioration of Agaricus bisporus Portobello was examined. Mushrooms were packed in four modified atmospheres and stored at 4 °C. Upon field research six quality attributes were transferred to ten characteristics. Quality function deployment was employed during a period of 22d.